Functionalization and informalization in the design of an online fashion shop. Issue 2 (April 2022) - van Leeuwen, Theo; Boeriis, Morten; Rytter Dakwar, Julia
This paper presents a multimodal analysis of the design of an online fashion shop. Departing from systemic-functional genre theory, it analyses the functionality of the site, bringing out how it designs what sellers do to and for consumers and what the site does and does not enable consumers to do. Drawing on Joos' analysis of (in)formality in language and Hall's proxemics, the paper then analyses how the site conceals the power of its functional design by simulating informality and solidarity in a way that ultimately remains one-way and cannot be reciprocated. It finally argues that designs of consumer behaviour similar to that of the analysed site increasingly stand as a model for the digitization of other domains of practice, including education and research, so extending what Fairclough called the 'marketization of discourse' into these other domains.